Rotor Suspension and Stabilization of Bearingless SRM using Sliding Mode Controller - V.S.Sobhan, Polamraju.; V. Nagesh Kumar, G; V. Ramana Rao, P (International Journal of Engineering and Technology, 2018)
Motors working in extreme conditions such as ultra high and low temperatures, high contamination, high purity etc. require high maintenance of mechanical bearings and the regular lubrication. Hence there is a need of a motor without mechanical bearings and lubrication in addition to simple in control and less maintenance. There by, bearingless motors (BLMs) gain more attention. The bearingless switched reluctance motorâ€™s (BLSRM)Â  is simple in construction and economical in addition to high speed capacity and high torque to inertia ratio. The magnetic nonlinearity arising due to double salient structure makes rotor eccentric displacement control and speed regulation complicate and needs robust control methodology such as sliding mode control (SMC) which has integrity, high certainty and rapid dynamic response when compared to typical controllers. Sliding mode can be realized with distinct classical reaching laws. This paper presents design and implementation of a SMC for a 12/14 BLSRM and the dynamic performance is endorsed by simulation using Matlab software.